Analisis Efektifitas Biaya Terapi Antibiotik Profilaksis Cefazoline dan Ceftriaxone pada Pasien Badan Penyelenggara Jaminan Sosial Kesehatan Rawat Inap Bedah Fraktur di RSU Madiun - Wika Admaja; Faldy Faldy; Anggi Restyana; Kumala Sari P.D.W (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2025)
In general, the treatment of fractures carried out is a surgical procedure, so the use of prophylactic antibiotic therapy is needed, including cefazoline antibiotics and ceftriaxone antibiotics. To determine the effectiveness value of the therapy outcome and the direct medical costs in patients who received prophylactic antibiotics cefazoline and ceftriaxone in fracture surgery cases in 2023 at Madiun Hospital. This study was conducted with an observational analytical approach and used a cross-sectional design carried out retrospectively using the provider's perspective. The study analyzed the direct medical cost and clinical outcomes is no incidence of surgical wound infection while the patient was receiving inpatient care at the hospital. Sampling was carried out using a purposive sampling technique. The research indicate that the direct medical cost of prophylactic cefazolin is IDR 10,517,114, while for ceftriaxone, it's IDR 10,027,158. Statistically, this difference was found to be significant with a p-value of 0.096. Regarding clinical outcomes, no surgical site infections were found with either cefazolin or ceftriaxone administration. Based on the direct medical costs incurred by patients and the clinical outcomes achieved, the Average Cost-Effectiveness Ratio (ACER) for cefazolin was calculated at IDR 10,517,114, and for ceftriaxone at IDR 10,027,158. Subsequently, the Incremental Cost-Effectiveness Ratio (ICER) was calculated, yielding a value of IDR 489,956. This suggests that using cefazolin is not more cost-effective than ceftriaxone, as the use of cefazolin would incur an additional cost of IDR 489,956 each treatment outcome. Antibiotic prophylactic cefazolin was not more cost-effective than ceftriaxone, with an ICER of Rp. 489,956.